PENGGUNAAN MEDIA VIRTUAL LAB TERHADAP MINAT BELAJAR FISIKA PESERTA DIDIK SMA NEGERI 10 PONTIANAK - Asshalihin Asshalihin; Stepanus Sahala; Syukran Mursyid (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine students' interest in learning physics inlearning onlinewithout using virtual lab learning media and by using virtual lab learning media, aswell as knowing the effect of students' interest in using virtual lab learning media ondynamic fluid material at SMA Negeri 10 Pontianak. The data was carried out bygiving a learning interest questionnaire to 28 students of class XI science at SMANegeri 10. The results of this study showed that students' interest in learning physicswithout using virtual lab learning media was in the medium category with an averageof 49,82 and interest in learning physics of students inlearning online using virtuallab learning media in the medium category with an average of 54,36. The results ofhypothesis testing show that there is a very significant influence on interest in learningin the use of virtual lab learning media with an increase in student interest in learningin the high category of 7,2% and in the medium category of 3,5%. The results of alldata analysis indicate that the use of virtual lab learning media in physics learninginlearning online at SMA Negeri 10 Pontianak can increase students' interest inlearning.Keywords: Learning Media, Interest in Learning, Virtual Lab